Formation evaluation for Mauddud Formation in Bai Hassan oilfield, Northern Iraq - K. Mohammed, Noor Alhuda; Farman, Ghanim M. (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Formation evaluation is a critical process in the petroleum industry that involves assessing the petrophysical properties and hydrocarbon potential of subsurface rock formations. This study focuses on evaluating the Mauddad Formation in the Bai Hassan oil field by analyzing data obtained from well logs and core samples. Four wells were specifically chosen for this study (BH-102, BH-16, BH-86, and BH-93). The main objectives of this study were to identify the lithology of the Mauddud Formation and estimate key petrophysical properties such as shale volume, porosity, water saturation, and permeability. The Mauddud Formation primarily consists of limestone and dolomite, with some anhydrites present. It is classified as a clean formation due to its low shale volume of approximately 17%. The results of the study show a low water saturation of around 30% and an effective porosity reaching up to 32% (with an average of 11%). The Mauddud Formation was further analyzed using the cluster analysis method, which identified four distinct hydraulic flow units (HFUs). The permeability of the Mauddud Formation was predicted using the flow zone indicator method, revealing a range from moderate to sound quality, averaging approximately 22 md.